Combination of spatial transcriptomics analysis and retrospective study reveals liver infection of SARS-COV-2 is associated with clinical outcomes of COVID-19Research in context - Shiqi Chen; Yi Zhang; Asha Ashuo; Shu Song; Lunzhi Yuan; Weixia Wang; Cong Wang; Zunguo Du; Yangtao Wu; Dan Tan; Chenlu Huang; Jingna Chen; et al. (EBioMedicine)
Summary: Background: Liver involvement is a common complication of coronavirus disease 2019 (COVID-19), especially in hospitalized patients. However, the underlying mechanisms involved are not fully understood. Methods: Immunohistochemistry (IHC) staining of SARS-CoV-2 spike (S) and nucleocapsid (N) proteins was conducted on liver tissues from six patients with COVID-19. The 10x Genomics Visium CytAssist Spatial Gene Assay was designed to analyze liver transcriptomics. TCR CDR3 sequences were analyzed in DNA from liver tissues. Liver function indicators were retrospectively studied in 650 hospitalized patients with COVID-19. Findings: SARS-CoV-2 proteins were initially detected in the livers of naturally infected golden (Syrian) hamsters, prompting us to investigate the situation in clinical cases. Thus, we collected liver tissues from patients with abnormal liver biochemical values. Viral S and N proteins were detected in the livers of severe and deceased patients but not in those of moderate patients. We further demonstrated that hepatocytes and erythroid cells in hepatic sinusoids are major cells targeted by SARS-CoV-2. Immune cells, especially T cells, were enriched in surviving severe patients, characterized by enhanced CDR3α clonality and novel CDR3β recombination of the T-cell receptor. In contrast, hepatocyte apoptosis was triggered, and the transcription of albumin (ALB) was obviously impaired in the deceased patients. We then performed a retrospective study including patients with COVID-19. Serum aspartate aminotransferase (AST) and ALB levels at baseline significantly differed in the deceased cohort. However, AST regression did not decrease the risk of death. ALB recovery indicated clinical improvement, and declining or low serum ALB concentrations were associated with death. Interpretation: This study provides clinical evidence for liver infection with SARS-CoV-2, insight into the impact of SARS-CoV-2 on the liver, and a potential way to evaluate the risk of death via assessing serum ALB concentration fluctuations in patients with COVID-19. Funding: National Key R&D Program of China (2021YFC2300602), National Natural Science Foundation of China (92369110), National Natural Science Foundation of China (U23A20474), Shanghai Municipal Science and Technology Major Project (ZD2021CY001), Shanghai Jinshan District Medical and Health Technology Innovation Fund Project (2023-WS-31).